CERVICO-FACIAL HEMANGIOMAS; THE TREATMENT THAT ELUDES US - Sharma, S.M. (Journal of Health and Allied Sciences NU, 2011)
Cervicofacial hemangiomas treated from January 2001 to December 2009 was clinically evaluated. This retrospective clinical study consisted of 42 females and 20 males with the age ranged from 20 days to 55 years. The lesions were present with-in first month in 45 patients (72.6%). Two patterns of tumor growth were evident: focal and diffuse. There were 59 focal hemangiomas (80.8%) and 14 diffuse hemangiomas (19.2%). Complications noted at the time of first consultation include residual skin changes in the in 35 patients (56.5%), obstruction of orifices in 14 patients (22.6%), ulceration in 6 patients (9.7%), and infection occurred in 2 patients (3.2%). Overall, there is reduction in size and improvement in color and texture of lesion following intervention in each group. No significant difference in outcome was observed in between groups with respect to change in size and texture. However, improvement in color showed statistically significant difference and combined treatment modality and surgical treatment was found to be better.
Keywords: Hemangioma; cervicofacia; management; challenges in treatment